The psychological stress of secondary school students in Vietnam - Vu Thi Khanh Linh, Phan Trong Ngo, Le Minh Nguyet, Khuc Nang Toan, (Opción, 2019)
The main goal of the research is to find out the stressful factors, levels of stress and possible interrelation between different factors in order to release stress influence. The research methodology is the self-assessment questionnaire and in-depth interview using Conners Comprehensive Behavior Rating Scales (Conners CBRS). The surveying results show that students are more stressed in the areas of studying, self-improving, body image and relationship with friends. In conclusion, when psychological stress arises, students use a variety of measures: accept and seek a coping solution; control and change emotion; try to avoid stress, etc.